Accounting for governmental and nonprofit entities - Hay, Leon E., Ph.D. CPA.; Wilson, Earl R., Ph.D., CPA. (USA : Irwin, 1991)
Financial Reporting for Governmental and Not-for-Profit Entities. Principles of Accounting and Financial Reporting for State and Local Governments. Capital Projects Funds. General Fixed Assets Account Group. Debt Service Funds. General Long....
Keywords: Accounting; Finance; Accounting; Finance